Musik Sebagai Stimulus Pada Kecerdasan Emosi Anak (Studi Kasus TK A Di Kelompok Bermain Kasih Ibu) - Siti Fadjryana Fitroh; Siti Mulifatin Khasanah (PG-PAUD Trunojoyo, 2016)
Emotional intelligence as of social intelligence that involves the ability to monitor feelings and emotions well in ourselves and in others, to sort out everything and use the information to guide your thoughts and actions. Emotional intelligence have a very important role for life Hence the need for an appropriate stimulus, one using music, where music is the element that is closest to human life. Music contains three components that can affect humans beat that can affect the body to move, which can affect the rhythm of life for listeners and harmonies can affect the human spirit to be calm and relaxed. The goal is to find out whether it's music affects the child's intelligence. Using descriptive qualitative research design using pieces of data penggumpulan method by observation techniques used to find the level of intelligence of children aspect, interviews to support the data from the observation and cekhlist note of observations and interviews. The results of this study indicate that there is a big impact on the use of music as a stimulus emotional intelligence of children, because of the results of this research children who have the aspect of high intelligence in kehidupanya accustomed to listening to good music from the habits of parents playing music and also the teacher often menuggunakan music in learning.